If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 462 = 42t + 4 Reorder the terms: 462 = 4 + 42t Solving 462 = 4 + 42t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-42t' to each side of the equation. 462 + -42t = 4 + 42t + -42t Combine like terms: 42t + -42t = 0 462 + -42t = 4 + 0 462 + -42t = 4 Add '-462' to each side of the equation. 462 + -462 + -42t = 4 + -462 Combine like terms: 462 + -462 = 0 0 + -42t = 4 + -462 -42t = 4 + -462 Combine like terms: 4 + -462 = -458 -42t = -458 Divide each side by '-42'. t = 10.9047619 Simplifying t = 10.9047619
| 5x+4(100-x)=100 | | 70(3x+10)=180 | | 70(3x+10)= | | 6y+4x= | | 48=2v+12 | | 7+3x=0.5(14+6x) | | z/7-9=3 | | t-17=20 | | 2x+5+2x+3x= | | 4(x-1)=-5(x+3)+32 | | -60x+32=Qx+p | | 5x+(2x-2)-(4x-3)= | | 3w+15=18 | | 3xy+9xy-5xy= | | 3(x-3)+2(x+2)=40 | | Y=4x^3-3x^2 | | F(x)=x^3-4x^2-5x | | 7(p+2)=-4(-4p-8) | | -2(5x+1)=-3-3x | | 3(5n-5)=-90 | | 9c=5(101)-160 | | z-10=28 | | -8(4x-3)+6x=-158 | | -8(3x+1)+5x=87 | | 91=7(-5a-2) | | 2n/3=11 | | -6(3x+5)=60 | | (9*9)-(8+4)= | | -6k+15=-5k+2k | | -10-(-63)= | | -117+4x=12x+107 | | (-5)+x=32 |